Spread of infection and treatment interruption among Japanese workers during the COVID-19 pandemic: A cross-sectional study - Akashi, Jun; Hino, Ayako; Tateishi, Seiichiro; Nagata, Tomohisa; Tsuji, Mayumi; Ogami, Akira; Matsuda, Shinya; Kataoka, Masaharu; Fujino, Yoshihisa (Frontiers in Public Health, 2022)
Background The COVID-19 pandemic has resulted in treatment interruption for chronic diseases. The scale of COVID-19 in Japan has varied greatly in terms of the scale of infection and the speed of spread depending on the region. This study aimed to examine the relationship between local infection level and treatment interruption among Japanese workers. Methods Cross-sectional internet survey was conducted from December 22 to 26, 2020. Of 33,302 participants, 9,510 (5,392 males and 4,118 females) who responded that they required regular treatment were included in the analysis. The infection level in each participant's prefecture of residence was assessed based on the incidence rate (per 1,000 population) and the number of people infected. Age-sex and multivariate adjusted odds ratios (ORs) of regional infection levels associated with treatment interruption were estimated by multilevel logistic models, nested by prefecture of residence. The multivariate model was adjusted for sex, age, marital status, equivalent household income, educational level, occupation, self-rated health status and anxiety. Results The ORs of treatment interruption for the lowest and highest levels of infection in the region were 1.32 [95 % confidence interval (CI) were 1.09–1.59] for the overall morbidity rate (per 1,000) and 1.34 (95 % CI 1.10–1.63) for the overall number of people infected. Higher local infection levels were linked to a greater number of workers experiencing treatment interruption. Conclusions Higher local infection levels were linked to more workers experiencing treatment interruption. Our results suggest that apart from individual characteristics such as socioeconomic and health status, treatment interruption during the pandemic is also subject to contextual effects related to regional infection levels. Preventing community spread of COVID-19 may thus protect individuals from indirect effects of the pandemic, such as treatment interruption.